Pengaruh Kepemimpinan Demokratis Kepala Ruang Rawat Inap Terhadap Kepuasan Kerja Perawat di Rumah Sakit Umum Aro Pekalongan - Broto Rahardjo; Chriswardani Suryawati; Farid Agushybana (Jurnal Manajemen Kesehatan Indonesia, 2019)
Leadership styles that are less suitable can reduce employee motivation, performance and job satisfaction. 4 out of 10 nurses in the inpatient room of Aro Pekalongan General Hospital felt dissatisfied with the leadership of the head of the inpatient room. Therefore a study was conducted to analyze the influence of the democratic leadership style of the inpatient head on the job satisfaction of nurses in Aro Pekalongan General Hospital.The study design was cross sectional with an observational quantitative approach. The research subjects were 32 nurses in the inpatient room of Aro General Hospital who were selected by the total sampling method. Data was collected by questionnaire. Processing and analysis of data using multiple logistic regression analysis.The results showed the variables of democratic leadership style related to nurse job satisfaction in Aro Pekalongan Hospital were delegation of responsibility variables (p = 0.005) and headroom decision-making variables (p = 0.034), while other variables not related to nurse job satisfaction were variable of headroom activity (p = 0.077) and empathy variable (p = 0.075). The variable delegation of tagging answers to the head of the room has a 19 times better effect on influencing nurse job satisfaction compared to the head of the room with poor delegation of responsibilities (p = 0.011 Exp (B) = 19.826).       It is recommended for management for periodic monitoring and evaluation, the selection of the head of the room is based on the length of work, competence and experience of advice for the head of the room to improve effective communication and hold regular meetings with nurses in the inpatient room of Aro Pekalongan General Hospital.